A boy with Burkitt lymphoma associated with Noonan syndrome due to a mutation in RAF1. Issue 6 (23rd April 2013) - Cianci, Paola; Tono, Valentina; Sala, Alessandra; Locatelli, Laura; Carta, Claudio; Rizzari, Carmelo; Biondi, Andrea; Selicorni, Angelo
Abstract This article reports on an association between Burkitt lymphoma and Noonan syndrome (NS) due to a RAF1 gene mutation. The patient was a 7‐year‐old boy with NS, who was included in the first series reporting the association between Noonan and RAF1, and who later presented with a 2‐week history of asymptomatic unilateral tonsillar swelling and ipsilateral cervical lymphadenopathy. Histological and biological examinations of the tonsillar biopsy led to the diagnosis of Burkitt lymphoma. While there is a well‐established association between NS and solid cell tumors, this is the first case described in the literature of Burkitt lymphoma in a patient with NS, and adds to the growing list of data supporting neoplasia's association with NS. © 2013 Wiley Periodicals, Inc.